Setting mitigation in the watershed context: demonstration and description of Colorado's watershed approach to compensatory wetland mitigation - Gilligan, Laurie, author; Johnson, J. Bradley, author; Lemly, Joanna M., author; Carlson, Erick, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2013)
In a comprehensive evaluation of wetland mitigation, the National Research Council (NRC) concluded that the goal of no net loss of wetlands is not being met for wetland functions by the U.S. Army Corps of Engineers (ACOE) and U.S. Environmental Protection Agency (EPA)'s mitigation program under Section 404 of the Clean Water Act (CWA). One of the key science recommendations of the NRC was for compensatory mitigation decisions to be made using a watershed approach Acknowledging this conclusion, the ACOE and EPA issued a federal rule in April 2008 to increase the effectiveness of compensatory mitigation and called for setting mitigation decisions in the watershed context. While requiring a watershed-scale view of mitigation, the new rule did not provide guidance on how a watershed approach should be implemented. At that time, Colorado lacked the basic capacity to carry out the watershed approach, particularly a lack of spatial data for wetlands and no single guidance document on procedures for applying the watershed approach. Through this project, we developed a process that would allow the watershed approach to be successfully and consistently implemented across the state. The overarching objective of this project was to demonstrate how the watershed approach can be implemented and used to inform CWA Section 404 decisions. Results from the Fort Range study area highlight the need to understand the current state of wetland resources when deciding what impact mitigation proposals will have on a watershed. The last objective of the study was to compare the FACWet and EIA methods of wetland assessment. While the two methods share similar goals of assessing the condition of wetlands, FACWet aims to measure functional condition (driven by physical processes) and EIA aims to measure biotic condition (the response to cumulative stress). The overall results of this project clearly illustrate the power and utility of data for making informed decisions about wetland regulation and management on a watershed scale. The provisional Colorado Watershed Approach guidance document will serve as a valuable tool for all parties involved in wetland mitigation, and we look forward to input from users in the coming year. Lastly, the comparison of assessment methods will clarify the relative strengths and utility of the two major wetland assessment methods currently in use in the state of Colorado.
Prepared for: U.S. Environmental Protection Agency, Region 8.
April 2013.
Keywords: Colorado; wetland classification systems; wetland mitigation; wetland profile; wetland mapping; watershed approach